2022
DOI: 10.3390/ph15030299
|View full text |Cite
|
Sign up to set email alerts
|

Old and New Biomarkers for Infection, Inflammation, and Autoimmunity in Treatment-Resistant Affective and Schizophrenic Spectrum Disorders

Abstract: Affective (AF) and Schizophrenic (SZ) Spectrum disorders manifest with risk factors, involving inflammatory processes linked to infections and autoimmunity. This study searched for novel biomarkers in cerebrospinal fluid (CSF) and peripheral blood. A total of 29 AF and 39 SZ patients with treatment-resistant disease were included. In CSF, the chemokine IL-8 was significantly elevated in AF and SZ patients. IL-8 promotes chemotaxis by neutrophils and may originate from different tissues. S100B, a glia-derived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
3
0
1
Order By: Relevance
“…Second, whereas the evidence of a possible increased inflammatory index in schizophrenia patients and changes after antipsychotics have been reported [ 329 ], there is a lack of information on the in vivo effects of antipsychotics on the inflammasome associated specifically with oxidative stress and free radicals’ production [ 330 , 331 ]. Therefore, more studies investigating peripheral biomarkers of oxidative stress before and after antipsychotic treatment should be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Second, whereas the evidence of a possible increased inflammatory index in schizophrenia patients and changes after antipsychotics have been reported [ 329 ], there is a lack of information on the in vivo effects of antipsychotics on the inflammasome associated specifically with oxidative stress and free radicals’ production [ 330 , 331 ]. Therefore, more studies investigating peripheral biomarkers of oxidative stress before and after antipsychotic treatment should be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Обнаружено, что содержание данного показателя в крови увеличивается при аутоиммунных заболеваниях [36]. В одном из недавних исследований у пациентов с шизофренией также установлен повышенный уровень sCD-25, что предполагает аутоиммунный характер воспаления при данном заболевании [37].…”
Section: материалы и методыunclassified
“…[ 86 ]. Studies have found abnormalities in the cytokine system in patients with TRS [ 87 , 88 ]. There is evidence that the levels of IL-2 and IL-6 were elevated in patients with TRS, which is probably associated with the activation of the inflammatory response system (IRS).…”
Section: Pathogenetic Aspect Of Inflammation In Treatment Resistance ...mentioning
confidence: 99%